Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2005)
Table of Content Wangechi Mutu, Re-Imagining the World by Isolde Brielmaier Orgies of Modernization: Jackum Nordström’s Exemplary World by Lytle Shaw Richard Serra Richard Serra in Bilbao by Hal Foster Walking and Looking on Videy Island by Kate D. Nesin Richard Serra’s List of Verbs by Theodora Vischer The Mind’s Mobility by Kenneth Baker Bernard Frize Art and Industry by Katy Siegel & Paul Mattick The Reconstitution of Time Past by Jordan Kantor The Politics of Colors by Patricia Falguières Katharina Grosse Uninhibited Thinking in Public Space by Gregory Volk Orly, Hans Ulrich Obrist in Conversation with Katharina Grosse Reflexive by Roman Kurzmeyer Jeremy Deller: For the Love of the People by Nato Thompson At Work, Lucy McKenzie by Dominic van den Boogerd Cosmic Fiction and Function: The Promise of Corey McCorkle’s Work by Christina Végh Trisha Brown: Esprit de Corps, Les Infos du Paradis by Louise Neri Learning at the Mission School, Cumulus from America by Lawrence Rinder A Story I Want to Believe, Cumulus from Anerica by Christy Lange
The art in this issue of Parkett is far-reaching. It reaches out physically and mentally; it occupies new territories and makes startlingly self-evident use of materials (Richard Serra); it leaves a traceable trail and takes permanent shape in abstract-concrete pictorial spaces and expanses of color (Bernard Frize); it moves lightly and in torrents, flooding into and over real, furnished rooms (Katharina Grosse). The result is not unexpected: concepts, ideas, and conventions are not only recalibrated, they are at times subjected to radical transformation. (editorial by publisher)
boek
Keywords: Frize, Bernard; Serra, Richard; Grosse, Katharina